2015
DOI: 10.3892/ol.2015.3492
|View full text |Cite
|
Sign up to set email alerts
|

A phase II double-blinded study to evaluate the efficacy of EW02 in reducing chemotherapy-induced neutropenia in breast cancer

Abstract: Abstract. EW02, a polysaccharide-enriched crude extract from black soybean, has been shown to assist hematopoiesis in chemotherapy-treated animals. The present study aimed to clarify the safety, quality of life (QOL) and efficacy for myelopoiesis of EW02 administration in early breast cancer (EBC) patients receiving adjuvant chemotherapy. A total of 60 eligible EBC patients were enrolled in a randomized, double-blinded trial, 40 of whom were prescribed 700 mg oral EW02 three times daily for 15 days in chemothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…Several studies showed that anthocyanins rich BSB have been shown to inhibit cancer cell growth by suppressing oxidative stress and inflammatory responses. Anthocyanin-rich BSB seed coat extract possibly reduces the development of tumors in various organs such as intestines [ 51 ], breast [ 109 ], prostate [ 65 , 110 ], stomach [ 80 ], ovary [ 111 ], endometrium [ 112 ], and liver [ 113 ]. In addition to the anthocyanins, saponins also prevent cancer cells from proliferation and spreading throughout the body [ 114 ].…”
Section: Health Benefits Of Anthocyanins Rich Bsbmentioning
confidence: 99%
“…Several studies showed that anthocyanins rich BSB have been shown to inhibit cancer cell growth by suppressing oxidative stress and inflammatory responses. Anthocyanin-rich BSB seed coat extract possibly reduces the development of tumors in various organs such as intestines [ 51 ], breast [ 109 ], prostate [ 65 , 110 ], stomach [ 80 ], ovary [ 111 ], endometrium [ 112 ], and liver [ 113 ]. In addition to the anthocyanins, saponins also prevent cancer cells from proliferation and spreading throughout the body [ 114 ].…”
Section: Health Benefits Of Anthocyanins Rich Bsbmentioning
confidence: 99%